Global Diversity Character Development Strategy at the Center for Indonesian Citizenship Education Klang Malaysia - Zuhana Ade Wirakusuma; Ardhana Januar Mahardhani; Hadi Cahyono; Ambiro Puji Asmaroini; Dwi Hatmoko (STAI Hubbulwathan Duri, 2023)
The issue of global diversity is an interesting one and must be introduced to native Indonesian students studying in Malaysia, one of whom is the Klang Malaysia Indonesian Citizen Education Center (PPWNI). The last study showed that seventh-grade students at PPWNI Klang, Malaysia, did not yet understand the meaning of global diversity. This study aims to describe the strategies of school principals and teachers to shape the character of global diversity in citizenship education and find out what diversity values are implemented in students. The research method used is descriptive-qualitative, with data collection through observation, interviews, and documentation. The analysis of research on students at the Indonesian Citizenship Education Center (PPWNI) in Klang, Malaysia, shows that the level of understanding of students still does not understand the meaning of global diversity. The activities carried out by school principals, teachers, and researchers in developing an attitude of global diversity in students by doing habituation at school, such as providing reading material on multicultural education, providing an understanding through Pancasila Education and Citizenship, and providing an understanding of global diversity through the media of global diversity posters. The implications of this research can make it easier for students to learn and understand individual differences and develop a tolerant attitude towards different people. Some of the results of the above activities that are most effective in providing students with an understanding of global diversity are achieved by using poster media, which can facilitate students' understanding of learning about differences and developing an attitude of empathy towards different people.